Management accounting and enterprise risk management. A potential integration as a new change in managerial systems. (2016) - Culasso, Francesca; Broccardo, Laura; Manzi, Luca Maria; Truant, Elisa
The main goals of this research are: 1) to understand if a further change in management accounting (MA) is required by changes in the contemporary extra-organisational environment, highlighting the main direction of this change, with particular attention to the integration with the enterprise risk management (ERM) as a new organisational institution; 2) to investigate if the management accountants' role should coherently evolve toward a deeper integration and coordination with that of risk managers, as an intra-organisational condition of success. The research method used is a qualitative mixed method, as it integrates inductive and deductive perspectives. In particular, we firstly used an empirical and comparative analysis based on explorative case studies. Secondly, our research adopted institutional theory, not with the intention of formally testing it, but rather to support our theoretical model of the successful directions of change.